Management of the COVID-19 pandemic: challenges, practices, and organizational support - Eman Kamel Hossny; Sahar Mohamed Morsy; Asmaa Mohamed Ahmed; Manal Saleh Moustafa Saleh; Atallah Alenezi; Marwa Samir Sorour (BMC, 2022)
Abstract Background Health organizations currently face tremendous challenges in the management of the COVID-19 pandemic. To do this, successful and proven scientific practices and support are needed. Aim This study aimed to explore the challenges, practices, and organizational support dealt with by nursing managers in the management of the COVID-19 pandemic. Method A qualitative content analysis study evaluated 35 nursing managers in five university hospitals through a semi-structured interview. The Consolidated Criteria for Reporting Qualitative Research were used for this qualitative study. Results Three main themes emerged: Challenges include the development of a COVID-19 crisis management plan, a shortage in nursing staff, and psychological problems. Practices include; changes in work schedules for nursing staff, the exchange process, hospital preparation, and training and education. And organizational support includes both support at an organizational level and support at an individual level. Conclusion This study revealed that nursing managers are faced with many challenges in the management of COVID-19, requiring good practices and organizational support. This study offers evidence for nursing managers to expect problems that may arise during the pandemic. Recommendations The COVID-19 pandemic requires the development of an integrated plan, and this plan must be disseminated to the hospital's nursing and medical teams to better equip them for the current and future crises.